PENGARUH MODAL, LAMA USAHA DAN PEMASARAN DIGITAL TERHADAP PENINGKATAN PENDAPATAN PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) KULINER - Nur Aina Desi Pratiwi; Zulgani; Yohanes Vyn Amzar (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This research purpose: 1) analyzing the socio-economic characteristics of culinary MSMEs in Kota Baru District, Jambi. 2) analyzing the influence of capital, business duration, and online marketing on the income of culinary MSMEs in Kota Baru District, Jambi. The analytical method used is quantitative descriptive analysis. The analytical tool uses multiple linear regression with EViews 12 data processing tools. The population in this study are culinary MSMEs in Kota Baru District, Jambi. Sampling uses a specific sample criteria selection method and produces a sample of 98 respondents. The results of this study found that: 1) Most culinary MSMEs in Kota Baru District are female, aged 18–35 years, have a high school education, are single, and generally do not have a number of dependents. The majority of respondents do not have a side job and run their own business. The initial capital used is an average of IDR 1,675,000, with an average monthly operational capital of IDR 2,493,316. The average net income is Rp5,425,000 per month, with an average business operating time of 8 hours per day. In addition, most culinary MSMEs have not utilized digital marketing as a product marketing medium. 2) The results of the study also found that capital, length of business, and online marketing together have a significant effect on the income of culinary MSMEs in Kota Baru District, Jambi. Individually, capital has a positive and significant effect on the income of culinary MSMEs in Kota Baru District, Jambi, while length of business and online marketing have a negative and significant effect on the income of culinary MSMEs in Kota Baru District, Jambi.